County Hospital Responses to Funding Reforms in Zhejiang, China: An Interrupted Time-Series Analysis - Tao Zhang; Jing Liu; Xiaohe Wang; Chaojie Liu (Taylor & Francis Group, 2023)
ABSTRACTThis study aimed to assess the effects of a two-stage funding reform, involving DRGs-based (Diagnostic Related Groups) payments for inpatient care and capitation funding for outpatient care, respectively, on services volume and care expenditure of county hospitals in Zhejiang province, China. A quasi-experimental design was adopted, involving 6 hospitals from 2 counties in the intervention group and 12 hospitals from 5 counties in the control group. The DRGs-based payments for inpatient care and capitation funding for outpatient care were introduced in January 2018 and January 2019, respectively. Controlled interrupted time-series analyses were performed to determine the effects of the funding reforms using monthly data over the period from January 2017 to December 2019. The volume of inpatient care decreased after the introduction of the first-stage DRGs-based payments, which was accompanied by an increase in the volume of outpatient visits. The DRGs-based payments led to a reduction of on average 1390 Yuan total expenditure per episode of inpatient care and 1116 Yuan out-of-pocket (OOP) payment per episode of inpatient care. However, the average outpatient expenditure per visit increased. So did the corresponding OOP payment per outpatient visit. The introduction of the second-stage capitation funding for outpatient care reversed the increasing trend of outpatient care. The average expenditure and OOP payment per outpatient visit decreased. The funding reforms create a significant effect on service volumes and expenditures in county hospitals. A coordinated approach to both inpatient and outpatient funding mechanisms is needed to minimize cost-shifting between inpatient and outpatient care and to achieve the intended policy outcomes.